2017
DOI: 10.1007/s11064-017-2220-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptors Protect Oligodendrocytes from Acute Ischemia in the Mouse Optic Nerve

Abstract: Studies by Bruce Ransom and colleagues have made a major contribution to show that white matter is susceptible to ischemia/hypoxia. White matter contains axons and the glia that support them, notably myelinating oligodendrocytes, which are highly vulnerable to ischemic-hypoxic damage. Previous studies have shown that metabotropic GluRs (mGluRs) are cytoprotective for oligodendrocyte precursor cells and immature oligodendrocytes, but their potential role in adult white matter was unresolved. Here, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Starting from this evidence, selective group I mGlu receptor agonists have been studied in periventricular leukomalacia, a condition characterized by OPC damage, that affects the white matter in premature infants after hypoxia-ischemia ( Jantzie et al, 2010 ). Butt et al (2017) demonstrated that group I receptor agonists can prevent hypoxia-ischemia-induced oligodendrocyte death at all stages of differentiation. Further studies are needed to establish the role of mGlu1 receptor as a new pharmacological target to prevent oligodendrocyte loss in neurodegenerative disorders such as MS, where OPCs are highly vulnerable to excitotoxic damage ( Newcombe et al, 2008 ).…”
Section: Group I Mglu Receptorsmentioning
confidence: 99%
“…Starting from this evidence, selective group I mGlu receptor agonists have been studied in periventricular leukomalacia, a condition characterized by OPC damage, that affects the white matter in premature infants after hypoxia-ischemia ( Jantzie et al, 2010 ). Butt et al (2017) demonstrated that group I receptor agonists can prevent hypoxia-ischemia-induced oligodendrocyte death at all stages of differentiation. Further studies are needed to establish the role of mGlu1 receptor as a new pharmacological target to prevent oligodendrocyte loss in neurodegenerative disorders such as MS, where OPCs are highly vulnerable to excitotoxic damage ( Newcombe et al, 2008 ).…”
Section: Group I Mglu Receptorsmentioning
confidence: 99%
“…However, other studies found that expression of all mGluRs proteins is strongly reduced in differentiated OLs compared to OPCs (Deng et al, ). Immunohistochemical studies in rodent white matter and human postmortem premature brain detected mGluR1/mGluR5 in OLs (Jantzie et al, ), while OLs in optic nerve explant cultures were shown to express mGluR3 and mGluR1/5 (Butt, Vanzulli, Papanikolaou, De La Rocha, & Hawkins, ). In cerebellar and callosal slices, the non‐selective mGluR agonist (1S,3R)‐ACPD evoked very small (5–10 pA) current in OLs (Karadottir et al, ).…”
Section: Glutamatergic Signaling Between Neurons and Oligodendrocytesmentioning
confidence: 99%
“…Administration of group I/II mGluR agonist in vivo significantly attenuates the loss of MBP and protects white matter in a rodent model of periventricular leukomalacia (Jantzie et al, ), however, it is unclear whether the protective effect is attributed directly to GalC + OLs, or to OPCs and their differentiation into OLs. Activation of either Group I or Group II mGluRs with specific agonists is also protective against oxygen–glucose deprivation in isolated postnatal optic nerves, but the beneficial effect is significantly reduced as animals mature (Butt et al, ). The observed protective effects of mGluRs may involve multiple mechanisms including activation of PKC, release of BDNF from OLs, as well as inhibition of adenylyl cyclase and reduction of cAMP levels (Bagayogo & Dreyfus, ; Butt et al, ).…”
Section: Functional Role Of Glutamate Receptors and Glutamatergic Sigmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the signaling pathway between mGluR activation and NRF2 nuclear localization remains unclear. Several phosphorylation pathways have been proposed to lie downstream of mGluRs, including PKC and PI3-kinase (Butt, Vanzulli, Papanikolaou, De La Rocha, & Hawkins, 2017; Codazzi et al, 2006; Hou & Klann, 2004; Zou et al, 2013), and Cdk5 and GSK3 have been shown to regulate NRF2 stability (X. Chen et al, 2016; Jimenez-Blasco, Santofimia-Castano, Gonzalez, Almeida, & Bolanos, 2015; Rojo, Sagarra, & Cuadrado, 2008), but the full pathway has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%